Effect of Heating Rate on the Dynamic Compressive Properties of Granite - Ronghua Shu; Tubing Yin; Xibing Li (Geofluids)
Variation in the heating rate due to different geothermal gradients is a cause of much concern in underground rock engineering such as deep sea and underground tunnels, nuclear waste disposal, and deep mining. By using a split Hopkinson pressure bar (SHPB) and variable-speed heating furnace, the dynamic compressive properties of granite were obtained after treatments at different heating rates and temperatures; these properties mainly included the dynamic compressive strength, peak strain, and dynamic elastic modulus. The mechanism of heating rate action on the granite was simultaneously analyzed, and the macroscopic physical properties were discussed. The microscopic morphological features were obtained by scanning electron microscopy (SEM), and the crack propagation was determined by high-speed video camera. The experimental results show that the dynamic compressive strength and elastic modulus both show an obvious trend of a decrease with the increasing heating rate and temperature; the opposite phenomenon is observed for the peak strain. The relationships among the dynamic compressive properties and temperature could be described by the quadratic function. The ductility of granite is enhanced, and the number and size of cracks increase gradually when the heating rate and temperature increase. The microstructure of rock is weakened by the increased thermal stress, which finally affects the dynamic compressive properties of rock.